Effect of Luseogliflozin on Heart Failure With Preserved Ejection Fraction in Patients With Diabetes Mellitus. Issue 16 (18th August 2020) - Ejiri, Kentaro; Miyoshi, Toru; Kihara, Hajime; Hata, Yoshiki; Nagano, Toshihiko; Takaishi, Atsushi; Toda, Hironobu; Nanba, Seiji; Nakamura, Yoichi; Akagi, Satoshi; Sakuragi, Satoru; Minagawa, Taro; et al.
Abstract : Background: Effects of sodium‐glucose cotransporter 2 inhibitors on reducing hospitalization for heart failure have been reported in randomized controlled trials, but their effects on patients with heart failure with preserved ejection fraction (HFpEF) are unknown. This study aimed to evaluate the drug efficacy of luseogliflozin, a sodium‐glucose cotransporter 2 inhibitor, in patients with type 2 diabetes mellitus and HFpEF. Methods and Results: We performed a multicenter, open‐label, randomized, controlled trial for comparing luseogliflozin 2.5 mg once daily with voglibose 0.2 mg 3 times daily in patients with type 2 diabetes mellitus suffering from HFpEF (left ventricular ejection fraction >45% and BNP [B‐type natriuretic peptide] concentrations ≥35 pg/mL) in a 1:1 randomization fashion. The primary outcome was the difference from baseline in BNP levels after 12 weeks of treatment between the 2 drugs. A total of 173 patients with diabetes mellitus and HFpEF were included. Of these, 83 patients were assigned to receive luseogliflozin and 82 to receive voglibose. There was no significant difference in the reduction in BNP concentrations after 12 weeks from baseline between the 2 groups. The ratio of the mean BNP value at week 12 to the baseline value was 0.79 in the luseogliflozin group and 0.87 in the voglibose group (percent change, −9.0% versus −1.9%; ratio of change with luseogliflozin versus voglibose, 0.93; 95% CI, 0.78–1.10; P =0.26). Conclusion: In patients with type 2 diabetes mellitus and HFpEF, there is no significant difference in the degree of reduction in BNP concentrations after 12 weeks between luseogliflozin and voglibose. Registration: URL: https://www.umin.ac.jp/ctr/index.htm ; Unique identifier: UMIN000018395.